The Influence of Sufism Traditions in Modern Society: A Literature Review - Indra Wijaya (Formad English Foundation NTB Jakarta, 2024)
Sufism traditions have become a significant foundation in shaping the spirituality of modern society, which faces the challenges of materialism and secularism. This study aims to analyze the influence of Sufism traditions on the spiritual life of modern society and the role of Neo-Sufism in addressing the spiritual crisis. Using a literature review method, this research examines various relevant primary and secondary sources. The findings reveal that Sufism significantly contributes to inner peace through practices such as dhikr (remembrance of God), meditation, and self-control. These traditions have adapted to modern contexts, including through spiritual workshops, Sufism-based communities, and digital applications. Neo-Sufism, as an innovation of Sufism, offers an inclusive approach relevant to modern life, such as integrating spiritual values into leadership and rejecting materialistic perspectives. This study concludes that Sufism traditions remain relevant as a spiritual solution to the crisis of meaning in life and provide a foundation for individuals and communities to achieve worldly and spiritual balance.